Utilization of Sludge from Water Treatment Plant as Fired Clay Brick - M.F.H. Sabahaudin; A.A. Kadir; A. Detho; M.I.H. Hassan; N.N.H. Hashar; N.F.N. Hissham (Archives of Metallurgy and Materials)
This study aims to establish the optimal percentage of water treatment sludge (WTS) for incorporation into fired clay bricks, assessing both physical and mechanical properties as well as heavy metal leachability. Fired bricks were produced with varying proportions of WTS (0%, 5%, 10%, 20%, and 30%). Compressive strength, density, shrinkage, and water absorption were examined to evaluate physical and mechanical properties. Toxicity Characteristic Leaching Procedure was employed to investigate heavy metal concentrations, focusing on inorganic constituents. Results indicated that the optimal ratio for WTS in fired clay bricks is 5%, aligning with industry standards (BS 3921:1985). The 5% sludge incorporation yielded bricks with impressive attributes: a peak compressive strength of 25.40 MPa, density within standard limits, water absorption below 20%, and firing shrinkage under 8%. Notably, aluminum content, predominant in the sludge, decreased significantly from 74.17 ppm to 4.97 ppm. These findings suggest that WTS, when integrated into fired bricks, emerges as a viable, cost-effective, and environmentally friendly alternative. The study underscores the potential of utilizing up to 5% WTS in fired clay bricks, presenting a promising avenue for sustainable construction practices.